2014
DOI: 10.1037/xlm0000004
|View full text |Cite
|
Sign up to set email alerts
|

Relatedness proportion effects in semantic categorization: Reconsidering the automatic spreading activation process.

Abstract: Semantic priming effects at a short prime-target stimulus onset asynchrony are commonly explained in terms of an automatic spreading activation process. According to this view, the proportion of related trials should have no impact on the size of the semantic priming effect. Using a semantic categorization task ("Is this a living thing?"), we show that on the contrary, there is a robust effect of relatedness proportion on the size of the semantic priming effect. This effect is not due to the participants using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(56 citation statements)
references
References 39 publications
(76 reference statements)
7
46
1
Order By: Relevance
“…De Wit and Kinoshita (2014) analyzed the RT distribution of the semantic-priming effect in the semantic categorization task. Participants classified target words as denoting “animals” (living things including birds, insects, fish as well as mammals) or “nonanimals” (man-made objects).…”
Section: Semantic-priming Effect In the Semantic Categorization Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…De Wit and Kinoshita (2014) analyzed the RT distribution of the semantic-priming effect in the semantic categorization task. Participants classified target words as denoting “animals” (living things including birds, insects, fish as well as mammals) or “nonanimals” (man-made objects).…”
Section: Semantic-priming Effect In the Semantic Categorization Taskmentioning
confidence: 99%
“…In two different semantic categorization tasks (affective valence decision and person–object decision), Voss et al observed that category-congruent primes facilitated decisions relative to incongruent primes, and that the effect manifested as a distributional shift 4. In addition, de Wit and Kinoshita (2014) showed that increasing the proportion of semantically related trials magnified the size of the semantic-priming effect and that this increase was constant across the range of response latencies (affecting only the μ parameter); that is, it increased the amount of distributional shift. De Wit and Kinoshita (2015a) then showed that the distributional shift pattern of semantic-priming effects is also found when the primes are presented very briefly and (forward- and) backward-masked, so that the participants are unaware of its identity.…”
Section: Semantic-priming Effect In the Semantic Categorization Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…This distributional shift has been interpreted to reflect a processing head start (Balota et al, 2008; Yap et al, 2013; for semantic categorization: De Wit & Kinoshita, 2014; 2015a) and as supporting the widely held belief that priming during visual word recognition is driven by the rapid prospective activation of related targets triggered by the prime. However, the current study shows that the observation, or lack thereof, of a distributional shift is strongly affected by the response time floor of the measure.…”
Section: Discussionmentioning
confidence: 55%
“…This head start mechanism would yield a semantic priming effect that is constant across the RT distribution. A pattern of semantic priming resulting solely from a distributional shift was also observed by De Wit and Kinoshita (2014; 2015a) for responses in a semantic categorization task. Similarly, the authors ascribe the distributional shift to a processing head start for related targets.…”
Section: Distributional Effects Of Semantic Primingmentioning
confidence: 65%